SUPPLIER DEVELOPMENT AND EXPORT PERFORMANCE OF OIL-SEED AGRO-PROCESSING FIRMS IN UGANDA - Aaron Ecel; Joseph Ntayi; Mohammed Ngoma (European Scientific Journal, ESJ, 2013)
The study sought to examine the relationship between supplier development and export performance of oil-seed agro processing firms in Uganda. Specific objectives were to examine the structure of supplier development activities, to establish the relationship between supplier development activities and export performance, the relationship between supplier development and opportunism, and the relationship between opportunism and export performance of agro-processing firms in Uganda. A cross sectional quantitative survey approach was adopted to undertake the study. A field study using proportionate stratified approach was used, involving a sample size of 50. Analysis of data involved the use of statistical package for social sciences (SPSS).The findings of the study revealed a significant and positive relationship between supplier development and export performance. The findings revealed no significant relationship between supplier development activities and opportunism and it revealed that opportunism is significantly and negatively related to export performance.